Increasing the Quantum Yield of Red Fluorescent Proteins Using Rational Design - Pandelieva, Antonia (Université d'Ottawa / University of Ottawa, 2016)
Monomeric red fluorescent proteins (RFPs) are used extensively for applications in molecular biology research, and are especially suited for whole body imaging applications due to their longer excitation and emission wavelengths, which are less damaging and penetrate deeper into animal tissue. However, these proteins suffer from reduced brightness compared to other fluorescent proteins, and require further engineering, which is often achieved through random methods, incurring large time and resource costs. Here we propose a rational design approach to improve the quantum yield of RFPs by reducing conformational variability of the chromophore. We engineered mRojoA, a mutant containing a π-stack involving Tyr197 and the chromophore phenolate, to include the P63F/H/Y mutations on its other side, by simultaneously mutating neighbouring positions 16, 143, and 163. The brightest mutants that we found in each library, mRojo-VYGV, mRojo-VFAV, and mRojo-VHSV, exhibited 1.8- to 2.4-fold increases in brightness, and quantum yield increases of up to 2.1-fold. In all three mutants, the increases in brightness were predominantly due to improvements in the quantum yield and not the extinction coefficient. Solving the crystal structures of two of these mutants along with a dim variant allowed us to strongly infer a link between rigidity of the chromophore and increased quantum yield. In addition, back-mutating position 63 in the highest quantum yield mutant, mRojo-VYGV, reversed the improvement in quantum yield, indicating that Y63 was the primary residue responsible for the improved brightness of the protein. Unfortunately, the mCherry-VYGV mutant did not achieve a similar increase in quantum yield or brightness. This is likely due to the lack of a second bulky aromatic residue at position 197, which is present in mRojoA. Nevertheless, this rational approach could be applied to some other RFPs whose chromophores exhibit increased conformational variability in order to further improve their brightness.
Keywords: rational design; red fluorescent protein (RFP); quantum yield; extinction coefficient; brightness; crystallography